Intensity invariant nonlinear correlation filtering for detection of camouflage patterns - Heng, Boon Hua. (2012)
Trying it to spot a camouflaged target in a forest far away is hard enough for us. Our naked eyes can only process these much to search and location an unknown target. Hence we need an equipment/ways to provide reliable and accuracy solution to handle this task.